CircRNA circ_0006892 regulates miR‐24/PHLPP2 axis to mitigate cigarette smoke extract‐induced bronchial epithelial cell injury. (3rd April 2021) - Zhang, Chenying; Gu, Shuangshuang; Kang, Xiuwen
Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic airway disorder mainly resulted from cigarette smoke exposure. The dysregulated circular RNAs (circRNAs) are relevant to the pathogenesis of COPD. This study aims to explore the function and mechanism of circRNA hsa_circ_0006892 (circ_0006892) in cigarette smoke extract (CSE)‐induced bronchial epithelial injury. The lung tissues were collected from 17 nonsmokers and 23 smokers with COPD. The bronchial epithelial cells (BEAS‐2B and 16HBE) were stimulated via CSE. Circ_0006892, microRNA‐24 (miR‐24), and PH domain and leucine‐rich repeat protein phosphatase 2 ( PHLPP2 ) abundances were examined via a quantitative reverse transcription polymerase chain reaction or Western blot. Cell viability, apoptosis, and inflammatory response were assessed via cell counting kit‐8 (CCK‐8), flow cytometry, and enzyme‐linked immunosorbent assay (ELISA). The target relationship of miR‐24 and circ_0006892 or PHLPP2 was tested via dual‐luciferase reporter analysis, RNA immunoprecipitation, and RNA pull‐down. Circ_0006892 expression was reduced in lung tissues of smokers with COPD and CSE‐stimulated bronchial epithelial cells. Circ_0006892 overexpression alleviated CSE‐induced viability reduction and promotion of apoptosis and inflammatory response. MiR‐24 was bound via circ_0006892, and miR‐24 overexpression reversed the effect of circ_0006892 on CSE‐induced injury. PHLPP2 was targeted via miR‐24, and miR‐24 knockdown mitigated CSE‐induced viability reduction and promotion of apoptosis and inflammatory response via regulating PHLPP2 . Circ_0006892 could promote PHLPP2 expression via regulating miR‐24. Circ_0006892 attenuated CSE‐induced bronchial epithelial cell apoptosis and inflammatory response via regulating miR‐24/ PHLPP2 axis. Abstract : Graphical abstract: Circ_0006892/miR‐24/PHLPP2 axis regulates CSE induced bronchial epithelial cell injury.